2018
DOI: 10.5535/arm.2018.42.6.846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound, Laser and Exercises on Temporomandibular Joint Pain and Trismus Following Head and Neck Cancer

Abstract: ObjectiveTo compare the effects of low intensity ultrasound (LIUS), traditional exercise therapy (TET), low level laser therapy (LLLT) and TET on temporomandibular joint (TMJ) pain and trismus following recovery from head and neck cancer (HNC).MethodsSixty participants following, who had experienced HNC, were randomly allocated to three groups of 20 people each. Each group received different therapy. Group A received LIUS and TET; group B received LLLT and TET; while group C received TET. All 60 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
0
10
0
8
Order By: Relevance
“…In the end, 11 eligible studies were included for systematic review. 18 - 28 Table 1 provides detailed characteristics of the included studies. All studies were published in English, used a randomized control design, and reported the effect of interventions to improve trismus following HNC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, 11 eligible studies were included for systematic review. 18 - 28 Table 1 provides detailed characteristics of the included studies. All studies were published in English, used a randomized control design, and reported the effect of interventions to improve trismus following HNC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of lowlevel laser therapy in patients with TMD seems to relieve pain and improves functional outcomes [29] or dysfunctional TMJ [30]. And in comparing the effects of different methods, low intensity ultrasound and traditional exercise therapy were more effective that laser therapy reduced TMJ pain and trismus after oncologic surgery [31].…”
Section: Treatment Of Tmdmentioning
confidence: 99%
“…The modern treatment concept of TMDs involves different modalities that are most often applied simultaneously or successively. Therapeutic modalities include pharmacotherapy, physical therapy, occlusal, surgical, behavioral therapy and psychotherapy [2,3].…”
Section: Introductionmentioning
confidence: 99%